Outcome and rehabilitation of patients following aneurysmal subarachnoid haemorrhage - Shukla, Dhaval P. (Journal of Neuroanaesthesiology and Critical Care, 2017)
Aneurysmal subarachnoid haemorrhage (SAH) is a dreaded neurosurgical disorder. Although the mortality has been declining in the past three decades, the disability after SAH is still significant. The main determinants of outcome are age, clinical grade, amount of SAH and size of aneurysm. Both neurophysical deficits and neuropsychological impairments are determinants of functional outcome after SAH. Patients should be assessed using outcome measures for both traumatic brain injury and stroke. Early rehabilitation after SAH improves not only physical outcome but also cognitive and functional outcome.
Keywords: Cognitive; neuropsychological; outcome; rehabilitation; subarachnoid haemorrhage